Musculoskeletal Diseases 2021-2024 Diagnostic Imaging - Hodler, Juerg; Kubik-Huch, Rahel A.; von Schulthess, Gustav K. (IDKD Springer Series, 2021)
This open access book focuses on imaging of the musculoskeletal diseases. Over the last few years, there have been considerable advances in this area, driven by clinical as well as technological developments. The authors are all internationally renowned experts in their field. They are also excellent teachers, and provide didactically outstanding chapters. The book is disease-oriented and covers all relevant imaging modalities, with particular emphasis on magnetic resonance imaging. Important aspects of pediatric imaging are also included. IDKD books are completely re-written every four years. As a result, they offer a comprehensive review of the state of the art in imaging. The book is clearly structured with learning objectives, abstracts, subheadings, tables and take-home points, supported by design elements to help readers easily navigate through the text. As an IDKD book, it is particularly valuable for general radiologists, radiology residents, and interventional radiologists who want to update their diagnostic knowledge, and for clinicians interested in imaging as it relates to their specialty.